E-Commerce, Motivation, and Self-Belief as Predictors of Entrepreneurial Intention Through Social Media Use - Halim Dwi Putra; Juwita Azizah; Soussou Raharimalala; Salim Diarra (Universitas Negeri Makassar, 2025)
This study examines the effects of e-commerce, motivation, and self-belief on entrepreneurial intention, with social media use serving as a mediating variable. A quantitative approach was employed using path analysis, and data were collected through questionnaires from respondents in a higher education context. The findings indicate that e-commerce has a significant positive effect on entrepreneurial intention, while social media use plays an effective mediating role in linking the independent variables to entrepreneurial intention. Motivation emerges as a key factor in strengthening entrepreneurial intention, whereas self-belief shows a more complex relationship that requires further consideration. The model explains 92.6% of the variance in entrepreneurial intention, highlighting the importance of integrating digital technology and social media platforms in fostering entrepreneurial aspirations among young people. These findings suggest that entrepreneurial intention in the digital era is shaped not only by motivational and psychological factors but also by the ability to engage with digital business platforms and social media environments. This study offers practical implications for entrepreneurship education and development programs seeking to encourage stronger entrepreneurial intention through digital exposure, platform familiarity, and more active social media engagement.